Blood flow distribution after end-to-side anastomosis with wide arteriotomy in extremity free flap surgery. Issue 10 (October 2021) - Motomiya, Makoto; Watanabe, Naoya; Nakamura, Shunichi; Kameda, Yusuke; Kawamura, Daisuke; Iwasaki, Norimasa
Summary: Purpose: Although many studies have investigated the optimal anastomotic procedure for the end-to-side (ETS) procedure with a free flap, no study has focused on the size of the arteriotomy. Some surgeons have recently described the effectiveness of ETS with wide arteriotomy, but the postoperative haemodynamics remains unclear for free flaps created using this technique. The aim of this study was to use ultrasonography to evaluate the postoperative blood flow distribution after ETS with a wide arteriotomy in extremity free flap surgery. Methods: We evaluated 20 free flaps in 18 consecutive patients who received an ultrasonographic examination after free flap surgery using the ETS technique with wide arteriotomy for arterial anastomosis. All flaps were examined after surgery and blood flow was calculated for the flap and recipient vessels. Results: All 20 flaps survived, but one flap developed asymptomatic arterial thrombosis and 19 flaps were analysed. For the ETS technique with wide arteriotomy, peripheral circulation was well preserved in all flaps. Comparison of flap types showed that blood flow was significantly higher in myocutaneous flaps than in fasciocutaneous flaps, but there was no significant difference according to the size of the arteriotomy. Conclusions: Given the range of arteriotomy performed using the ETS with a wide arteriotomy technique, the blood flow volume in the flap depended on the type of flap but not on the size of the arteriotomy. A steal phenomenon related to the creation of a wide window in the receipt artery was not found in the analysed retrospective cohort.